ENTREPRENEURSHIP EDUCATION AS A PANACEA FOR JOB CREATION AND MITIGATING THE EFFECT OF UNEMPLOYMENT - Sani, Hussaini A. B (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2025)
Entrepreneurship education has been a vital solution to the difficult problem of unemployment and job creation. The present study examines the potential of entrepreneurship education in addressing the controversial issues of job creation and unemployment in Nigeria. With the provision of required skills, knowledge, and capacities, entrepreneurship education makes people self-employed as well as employable. The study observes the benefits of entrepreneurial education, including the creation of employment, minimization of unemployment, and encouragement of sustainable development. The study also identifies the need for responding to changing skill requirements and nurturing an entrepreneurship ethos. The findings observe that entrepreneurial education can play a major role in mitigating the effects of unemployment and aiding economic growth, innovation, and self-sufficiency. Through investment in entrepreneurial education, individuals, communities, and nations can create new economic opportunities and prosperity. It provided possible solutions to the challenges, and therefore conclusion were drawn. It was however recommended that the government should give adequate attention to entrepreneurial development in the country through the provision of good economic environment to encourage individual participation in business. While this is guaranteed, entrepreneurship will thrive and consequently create jobs and mitigate the effects of unemployment of graduate in Nigeria.